PENGARUH KEGIATAN EKSTRA KURIKULER PRAMUKA DAN PMR TERHADAP HASIL BELAJAR SISWA ( STUDI DI SEKOLAH DASAR NEGERI 1 PASIR KECAPI DAN SEKOLAH DASAR NEGERI 2 SANGIANG) - Sarbendi, Sarbendi; Wulandari, Dewi (Jurnal Ilmiah Pendidikan dan Keislaman, 2021)
Extracurricular activities are a series of programs of teaching and learning activities outside of programmatic lesson hours, which are intended to increase the horizon of students' views, foster talent and interest and spirit of community service. For example: in scouting activities and the youth red cross (PMR) is a form of activity that develops many humanitarian activities. This study aims to find out if there is an influence of scout extracurricular activities on student learning outcomes. To find out if there is an influence of adolescent red cross activities (PMR) on student learning outcomes. To find out if there is an influence of extracurricular activities of scouts and PMR on student learning outcomes in public elementary school 1 pasir lute and public elementary school 2 sangiang. The results of the Extracurricular Scout and Extracurricular PMR variables had a partially significant effect on Student Learning Outcomes. Evidenced by the magnitude of the Scout Extracurricular regression coefficient of 0.546 and extracurricular PMR of 0.518 with a significant value of 0.000 (0.000<0.05). There is an influence of scout extracurricular activities (X1) on student learning outcomes in state schools 1 sand lute and public elementary school 2 sangiang, this is evident from the results obtained that the regression value (t count) for variable X1 (scout extracurricular activities) is 4,478, while the t table value for N = 40 is 2,026. so 4,478 > 2,026,  It can be concluded that partially variable extracurricular activities of scouting do have a positive influence on students' learning outcomes.. There is an influence of PMR (X2) extracurricular activities on student learning outcomes in state schools 1 sand lute and public elementary school 2 sangiang, this is evident from the results obtained that the regression value (t calculate) for variable X2 (PMR extracurricular activities) is ,484, while the t table value for N = 40 is 2,026. So 4,848 > 2,026, it can be concluded that partially variable extracurricular activities PMR does have a positive influence on student learning outcomes. Extracurricular activities of scouting and PMR together (simultaneously) affect the learning outcomes of students in public elementary school 1 sand lute and public elementary school 2 sangiang. This is evident from the results obtained that the value of f calculated at 35,071 which is greater than the f table of 3,250 or 35,071 >3, 250 with a significant level of 0.000 < 0.05, it can be said that the extracurricular activities of scouting (X1) and variable PMR (X2), together have an effect on the variable learning outcome (Y). This showed that 65.5% of scout and PMR extracurricular activities simultaneously (together) did have a positive effect on students' learning outcomes while the remaining 34.5% had an effect on other factors not studied in the study